Peculiarities of Dissemination and Functioning of Incunabula: Cases of Collections of Lithuanian Memory Institutions - Vaitkevičiūtė, Viktorija (Knygotyra, 2020)
Incunabula are considered a particularly important part of the documentary heritage. 520 incunabula are preserved in eight different Lithuanian memory institutions. The engagement of Lithuanian libraries in the development of the international database of incunabula provenances, Material Evidence in Incunabula (MEI: https://data.cerl.org/mei/_search), intensified research on incunabulistics, as it led to a closer examination of the marks of the former owners. The article presents the latest data on the distribution of incunabula in different Lithuanian memory institutions, as well as analyzes various book marks that were not recorded in Nojus Feigelmanas’ catalog of Lithuanian incunabula or was revised and supplemented, and evaluates their significance in the printed book culture of the Grand Duchy of Lithuania. The analysis is performed using the provenance method, however is not limited to property marks, but also includes margins – marks left by a reader on the pages of books, and other marks not related to property or reading, providing significant information on book history, culture and peculiarities of reading at that time.In the 15th century, there were no printing houses in the Grand Duchy of Lithuania, so the main spread of books was by trade. The entries with prices identified in the incunabula reveal a relatively early time of purchase of the incunabula and testify that the books in the 16th-17th centuries were an expensive commodity. They usually mention groschen, the common currency in the territory of Lithuania-Poland, less often – florins or ducats. In this case, the large variety of prices does not allow to draw more specific conclusions on the prices of incunabula in the relevant period, but these data as a source of book history will serve in general when studying the value of the old books and the circumstances of their acquisition. Purchase records usually also provide information about a former owner of a book. The article focuses more on lesser-known owners on whom new information has been found or existing data have been updated, attention is also paid to female donators. The article also discusses the records left by the incunabula rubricators, which allows to determine the period of the book entry into the Grand Duchy of Lithuania, as well as to look at them as one of the first readers.Various inscriptions left by anonymous owners require the most effort. Entries of the 15th-16th centuries, mostly in Latin, many of which are abstracts of an existing book or notes on it, additions to the text, are still awaiting detailed reading and research. Identified Lithuanian words will be a valuable source of the language history for researchers of the old Lithuanian language. Various marginalia – reviews on a book, notes from everyday life, counting the year of the book, as well as graffiti, different drawings that can be seen as feather attempts, amateur illustrations, caricatures or even as an expression of reading boredom, will be an important material to describe a reader’s relationship to the book at the time, for which the incunabula, like books of other ages, were not only the object of study or research, but also a kind of notebook for important thoughts, synopses, everyday details.
Keywords: the 15th century book; incunabula; provenances; rubricators; personal libraries; prices; database MEI